To solve the equation \(3x + 5y = 60\) for \(y\), follow these steps:
-
Subtract \(3x\) from both sides:
\[ 5y = 60 - 3x \]
-
Now divide both sides by \(5\) to isolate \(y\):
\[ y = \frac{60 - 3x}{5} \]
-
This can be simplified to:
\[ y = 12 - \frac{3}{5}x \]
None of the answers directly match this simplified form, but the equivalent expression can be interpreted as:
- Correct expression: \(y = 12 - \frac{3}{5}x\)
Among the options you provided:
- \(y = 60 - 3x\) is not correctly rearranged as it misses the denominator of 5.
- \(y = \frac{60 + 3x}{5}\) is incorrect.
- \(y = \frac{-3}{5}x + 12\) matches our derived expression but appears in a different order.
- \(y = 57x5y\) is not related to the equation.
The correct expression appears to be \(y = 12 - \frac{3}{5}x\).
If you see:
- The response that translates to \(y = -\frac{3}{5}x + 12\) is equivalent to my derived expression.
Therefore, the final answer is:
y = -3/5x + 12.